Human rights-based community practice in the United States - Libal, Kathryn, 1968-; Harding, Scott (2015)
"A transformative model for community social work rooted in basic social and economic rights is the basis of this timely Brief. With specific chapters spotlighting the rights to health care, nutritious food, and adequate and affordable housing, the book describes in depth the role of community practice in securing rights for underserved and vulnerable groups and models key aspects of rights-based work such as empowerment, participation, and collaboration. Case examples relate local struggles to larger regional and statewide campaigns, illustrating ways the book's framework can inform policymakers and improve social structures in the larger community. This rights-based perspective contrasts sharply with the deficits-based approach commonly employed in community social work, and has the potential to inspire new strategies for addressing systemic social inequality"--Publisher's website.
Human rights-based approaches to community practice in the United States : a call to action -- Mobilizing for the right to health and health care -- More than a commodity : the right to adequate housing -- Building a movement to recognize food security as a human right in the United States -- Community practice, fostering participation, and human rights.
Includes bibliographical references (pages 85-95).
Keywords: Community development -- United States; Human rights -- United States; Community development; Human rights; United States